Analisis Persediaan Minyak Goreng Pada Bulog Divisi Regional Sulawesi Utara - Homer, Rafael Stanly; Loho, Agnes Estephina; Tangkere, Ellen Grace (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2024)
This study aims to analyze the supply of cooking oil at Bulog North Sulawesi Regional Division. This research was conducted from May to June 2023. The data used in this research is secondary data. Secondary data is data that has been arranged in written form obtained from the company directly. The data is then processed and calculated using the EOQ method. The results of this study indicate that the procurement of cooking oil at Bulog North Sulawesi Regional Division is not optimal. The frequency of cooking oil procurement carried out by Bulog North Sulawesi Regional Division during 2023 was 28 times, while the results of calculations using EOQ obtained an order frequency of 6 times a year. This means that when using EOQ calculations can minimize ordering costs. The EOQ calculation also obtained the maximum amount that can be managed.